2014
DOI: 10.1186/1471-230x-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of COX-2 mRNA in colorectal cancer

Abstract: BackgroundCyclooxygenase-2 (COX-2, PTGS2) is an enzyme involved in the synthesis of prostaglandins and thromboxanes, which are regulators of biologic processes such as inflammation, cell proliferation and angiogenesis. COX-2 over-expression was reported in many (pre) malignant tissues, but data strongly vary and seem to depend on the methodology used.MethodsNormal colorectal mucosa and paired cancerous tissue from 60 patients with colorectal cancer was investigated for the levels of COX-2 mRNA by real-time qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(151 citation statements)
references
References 27 publications
15
131
1
4
Order By: Relevance
“…When comparing diagnostic accuracy for Marsh 0–1 vs Marsh 2–3 lesions, there were 9 24,25,28,29,41,44,45,47,48 eligible studies of tTG IgA (479 patients; 25% Marsh 2–3 lesions; see supplementary figure S2). Sensitivity of tTG IgA ranged from 0.16 to 0.79 and specificity ranged from 0.68 to 0.99.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing diagnostic accuracy for Marsh 0–1 vs Marsh 2–3 lesions, there were 9 24,25,28,29,41,44,45,47,48 eligible studies of tTG IgA (479 patients; 25% Marsh 2–3 lesions; see supplementary figure S2). Sensitivity of tTG IgA ranged from 0.16 to 0.79 and specificity ranged from 0.68 to 0.99.…”
Section: Resultsmentioning
confidence: 99%
“…The deletion of a single allele causes 34% reduction, whereas a complete knockdown causes 86% reduction in the number of intestinal polyps in APC 716 knockout mice 65 . Increased levels of both COX-2 and prostaglandin E 2 (PGE 2 ), which is the enzymatic product of COX-2, are found in CRCs [66][67] . Another study found 51 SNPs in HPGD, SLCO2A, and ABCC4 aside from Cox-2, which code for 15-PGDH (Cox-2 antagonist), MRP4 (Cox-2 transporter), and PGT (Cox-2 transporter), respectively.…”
Section: Mutational Landscape In Chromosomal Instabilitymentioning
confidence: 99%
“…A real-time quantitative RT-PCR assay was performed with FastStart Essential DNA Green Master (Roche Applied Science, Indianapolis, IN, USA) and the LightCycler Nano (Roche Diagnostics, Mannheim, Germany). Primers for the PCR of β-actin, COX-2, and CHIP were taken from previous studies (Wu et al, 2003;Shigematsu et al, 2009;Roelofs et al, 2014). The reaction conditions for COX-2 were 95°C for 10 min, followed by 45 cycles at 95°C for 10 sec, at 58°C for 10 sec, and 72°C for 15 sec, and for CHIP were 95°C for 10 min, followed by 45 cycles at 95°C for 10 sec, at 60°C for 10 sec, and 72°C for 15 sec.…”
Section: Analysis Of Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%